Wrigley's Eclipse gum : managing brand adolescence - Lee, Angela Y.; Merkley, Greg; Bailey, Bob ([London] : SAGE, 2016)
Wrigley launched Eclipse gum in August 1999. In early 2000, Paul Chibe became senior marketing manager for Wrigley's breath freshening portfolio, which included Eclipse. With the disappointing first-year performance of the brand, Chibe needed to take action to turn Eclipse around. His task was to use the opinions from other Wrigley executives and from marketing research data to decide if Eclipse could be turned around or if it should be abandoned.
Originally Published in: Lee, A. Y., Merkley, G., & Bailey, B. (2015). Wrigley's Eclipse Gum: Managing Brand Adolescence (teaching notes revised 08/04/2015). 5-414-752. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Wm. Wrigley Jr. Company; Brand name products -- Case studies; Marketing -- Management -- Case studies